2010
DOI: 10.1007/s00044-010-9383-5
|View full text |Cite
|
Sign up to set email alerts
|

Dodecanoic acid derivatives: Synthesis, antimicrobial evaluation and development of one-target and multi-target QSAR models

Abstract: In this study a series of dodecanoic acid derivatives (1-30) were synthesized and evaluated for in vitro antimicrobial activity against the panel of Gram positive, Gram negative bacterial and fungal strains. 4-Nitro phenyl dodecanoate (4) and quinolin-8-yl dodecanoate (5) emerged as most effective antibacterial agents, and 1-(4-benzylpiperazin-1-yl) dodecan-1-one (15) was found to be the most effective antifungal agent amongst the synthesized dodecanoic acid derivatives. Quantitative structure activity relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In bioactivity studies, the honeybee Apis mellifera has been reported as producing the compounds associated with compounds 1, 7, 12, and 13, which are utilized in the queen fecal pheromones involved in nestmate recognition (Breed et al, 1992). Recently, the two laurates described as compounds 7 and 9 were evaluated for in vitro antimicrobial activity against the panel of Gram positive and Gram negative bacterial and fungal strains in quantitative structure activity relationship (QSAR) studies (Sarova et al, 2011). n-Hexyl Table 2 Constituent carboxylic acid and alcohol, and structures of fifteen esters from Anaulaciulus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In bioactivity studies, the honeybee Apis mellifera has been reported as producing the compounds associated with compounds 1, 7, 12, and 13, which are utilized in the queen fecal pheromones involved in nestmate recognition (Breed et al, 1992). Recently, the two laurates described as compounds 7 and 9 were evaluated for in vitro antimicrobial activity against the panel of Gram positive and Gram negative bacterial and fungal strains in quantitative structure activity relationship (QSAR) studies (Sarova et al, 2011). n-Hexyl Table 2 Constituent carboxylic acid and alcohol, and structures of fifteen esters from Anaulaciulus sp.…”
Section: Discussionmentioning
confidence: 99%
“…While in addition, the temperature was maintained at 0-10 0 C. The stirring was performed for 30min, and the precipitated amide was separated by filtration. The recrystallization of crude amide was done from alcohol 20 .…”
Section: Step 2: Formation Of Acid Chloridementioning
confidence: 99%
“…Sarova et al [ 14 ] synthesized three dodecanoic acid derivatives 1 − 3 with yields of 59–61 % , starting from dodecanoic acid in two steps, chlorination with thionyl chloride and reaction with the corresponding aminopyridine ( Scheme 1 ). All compounds possessed good antibacterial activity against B. subtilis , S. aureus and E. coli and antifungal activity against A. niger and C. albicans .…”
Section: Synthesis Of Antimicrobial Compounds Containing Only Pyridin...mentioning
confidence: 99%